Acute Pancreatitis as a Rare Initial Manifestation of Wegener's Granulomatosis. A Case Based Review of Literature - Chawla, Saurabh; Atten, Mary Jo; Attar, Bashar M (JOP. Journal of the Pancreas, 2011)
Context Vasculitis is a known cause of pancreatitis and other gastrointestinal symptoms; however, most of these patients have medium vessel vasculitis like polyarteritis nodosa and often there are other associated conditions like hepatitis B or clinical manifestations that suggest the diagnosis. Wegener’s granulomatosis is predominantly a reno-pulmonary disorder, rarely having gastrointestinal manifestations. Case report We report a case of Wegener’s granulomatosis initially presenting as acute pancreatitis and then rapidly progressing to severe multi-organ involvement over the next few months. Discussion Pancreatic association as an initial presentation of Wegener’s granulomatosis is limited to only a few reports. This extremely rare initial presentation makes the diagnostic process challenging. Two different pancreatic manifestations have been reported: as a pancreatic mass mimicking a tumor or as acute pancreatitis. The patients who presented as pancreatic head masses underwent extensive surgical procedures before the diagnosis was established. Acute pancreatitis as the initial presentation is usually associated with an aggressive course of the vasculitis and often results in a fatal outcome. Conclusions This case illustrates Wegener’s granulomatosis as a rare cause of acute pancreatitis. It emphasizes the need for thorough continued systemic clinical evaluation of patients when the etiology is not readily evident. Also, since most patients with pancreatitis due to Wegener’s granulomatosis rapidly progress to severe multiorgan involvement, knowledge of a broad differential of potential etiologies and a low index of suspicion is required for timely diagnosis and treatment. Image: John H. Stroger Jr., Hospital of Cook County. Chicago, IL, USA.